Implementasi Dakwah Melalui Komunikasi Interpersonal Dalam Novel Si Anak Pintar Tere Liye - Aslikhatul Ummah Sofi Alif (Program Studi Komunikasi dan Penyiaran Islam Fakultas Dakwah UIN Sultan Maulana Hasanuddin Banten, 2023)
The novel Si Anak Pintar contains a message of da'wah through interpersonal communication that wants to invite someone to do good and bad deeds, especially for small children, teenagers, and adults. This article is library research and a type of qualitative research. The data analysis used is content analysis. Research data by reading, recording, and collecting stories containing the implementation of da'wah carried out by parents and residents of the village of Si Pukat and their friends using interpersonal communication theory. The results obtained include: 1) Interpersonal Communication in the form of Openness which includes prohibiting starting a fight if you don't know how to end it, don't let honesty go away from young people because of environmental influences, and don't like to talk about other people. 2) Interpersonal communication in the form of Empathy (empathy) includes the importance of appreciating a grain of rice and eating according to its portion. 3) Interpersonal Communication in the form of Supportiveness includes matters of earnest learning, there is no simplicity and if you want to be a good writer, start by writing. 4) Interpersonal Communication in the form of a Positive Attitude includes those who are trained to do mathematics, children must always be disciplined, honesty is everything and a ban on fighting for more than three days. 5) Interpersonal communication in the form of equality (equality) includes honesty that can improve temperament and family, friends, and the environment that can affect temperament.